Valores de albúmina sérica y relación con las complicaciones y mortalidad de pacientes en hemodiálisis del Hospital Isidro Ayora, Loja - Encalada Montaño, Juan Gabriel (2020)
Hypoalbuminemia (value less than 3.5mg/dL) being associated to patients on hemodialysis constitutes a cause of morbidity and mortality around the world. The present study called "Values of serum albumin and relationship with complications and mortality of patients on hemodialysis at the Hospital Isidro Ayora, Loja" was carried out a descriptive, prospective study with a quantitative and cross-sectional approach, whose objective is to establish the existing relationship of serum albumin values with complications and mortality in patients undergoing hemodialysis, classify patients according to age and sex, identify the most frequent complications, mortality and their relationship. After collecting the information, the following results were obtained: 58 patients studied, from which 15 presented complications associated with hypoalbuminemia, 60% (n = 9) belonged to the age group between 60 - 69 years and the majority belonged to male sex with 87% (n=13). The predominant complication was Community Acquired Pneumonia 44% (n = 8), followed by Sepsis 22% (n = 4). The albumin value of patients who presented complications was in the range of 3.1 g / dL-3.4 g / dL, 83% (n = 15). Therefore, there was a directly proportional relationship between hypoalbuminemia and complications in patients undergoing hemodialysis, so this pathology must be identified early to correct the values and so avoid morbi-mortality of patient. Key words: hypoalbuminemia, hemodialysis, complication, mortality